Show how to derive the quadratic formula

You have a general quadratic of the form: ax^2 + bx + c = 0, where a,b,c are constants (although is consistent for functions). Divide by a (assuming a/=0, this would not be a quadratic in that case):x^2 + (b/a)x + c/a = 0Complete the square on the first 2 terms:(x+(b/2a))^2 - (b/2a)^2Add the 3rd term back on:(x+(b/2a))^2 - (b/2a)^2 + c/a = 0Rearrange to have the x term on its own:(x+(b/2a))^2 = (b/2a)^2 - c/aTake the square root:x+(b/2a) = +/-sqrt{(b/2a)^2 - c/a}Subtract b/2a:x = -b/2a +/- sqrt{(b/2a)^2 - c/a}Putting the right hand side over a common denominator:x = [-b +/- sqrt{b^2-4ac}]/2a

Answered by Tom F. Maths tutor

2890 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Let f(x)=e^x sin(x^2). Find f'(x)


Differentiate x^(1/2)ln(3x) with respect to x.


Why does d/dx (tan(x)) = sec^2(x)?


Given that y = 4x^3 -1 + 2x^1/2 (where x>0) find dy/dx.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences